IDENTITAS KOLEKTIF AMERIKA SERIKAT DAN MEKSIKO DALAM MERIDA INITIATIVE 2008 UNTUK MENANGGULANGI PEREDARAN GELAP NARKOTIKA (PERIODE 2008-2014) - Maulidyatama, Muhammad Ginong; Utomo, Tri Cahyo; Rosyidin, Mohammad (Journal of International Relations, 2016)
The Merida Initiative 2008 showed the anomalous relationship between UnitedStates and Mexico that have a history of disharmonious relationship overhundreds of years ago. In addition, this study also aims to determine the effortsthat have been made between United States and Mexico in implementing thepoints of agreement on the Merida Initiative 2008. Using constructivismparadigm of collective identity, the research method used in this research isdescriptive explanatory method with the variable dependent lies on thecollective identity of the United States and Mexico under the Merida Initiative,and the independent variables lies on three determinants of collective identity,which are structural, systemic and strategic factors. Merida Initiative can beregarded as an effective cooperation, since the two countries haveimplemented the points of agreement in this cooperation positively. It ischaracterized by the high number of drug seizures, arrested officials of drugcartels, and the continuation of this cooperation. United States and Mexicoalso described Merida Initiative as a new paradigm in their securitycooperation. Merida Initiative has successfully renew the relationship betweenthe two countries, especially in diplomatic relations on security cooperation.